Asymmetrics in ordered strength of preference models: implications of focus shift for discrete-choice preference estimation. - Johnston, Robert J.; Swallow, Stephen K. (Land Economics, 1999)
A study was conducted to examine potential focus-shift asymmetries in an ordered-strength-of-preference model applied to contingent choice data. A focus shift takes place when respondents weight factors differently when evaluating preference for an “accepted” scenario than they do when evaluating preference for a “rejected” scenario and may imply that respondents do not refer to a single underlying preference function. Using data drawn from a survey that addressed preferences for watershed management, the model findings identified focus-shift asymmetries in the ordered-strength-of-preference model.